PREVALENCE AND DIETARY DETERMINANTS OF ANAEMIA AMONG YOUNG ADULTS AGED 18–25 YEARS: A CROSS-SECTIONAL SURVEY AT A TERTIARY CARE INSTITUTION IN SOUTH INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Anaemia continues to affect a substantial proportion of young adults in India despite expanding nutrition policy. Local determinants, particularly dietary patterns and the gap between awareness and behaviour, in tertiary-care young-adult populations of South India are not well quantified. Objectives: To determine the prevalence of anaemia and the distribution of haemoglobin levels among young adults aged 18–25 years, evaluate associations between dietary habits and haemoglobin status, identify dietary patterns contributing to low haemoglobin, and assess the level of awareness regarding nutrition and anaemia. Methods: Single-centre, cross-sectional observational survey conducted between January 2024 and December 2024 at a tertiary care institution in South India, enrolling 194 young adults aged 18–25 years. Data was collected through a self-administered Google Form. Analyses used IBM SPSS Statistics v26, chi-square or Fisher's exact tests for bivariate associations, and binary logistic regression for adjusted analysis. α was set at 0.05, two-tailed. Results: Among the 194 participants, the prevalence of anaemia was 45.9% (89/194; 95% CI 39.0–52.9%), with a mean haemoglobin of 11.94 ± 1.78 g/dL. Anaemia was more prevalent in females (54.0%) and was predominantly mild (48.3%) or moderate (50.6%); severe anaemia (1.1%). In multivariable logistic regression, three variables independently predicted anaemia: female sex (aOR 4.47, 95% CI 2.03–9.84; p